Evaluasi Tingkat Kesesuaian Lahan Aktual dan Potensial untuk Budidaya Bawang Merah (Allium cepa L.) di Desa Lampoko Kabupaten Bone - Muh. Alif Akbar Barsut; Sulkifli Sulkifli (Jurnal Agrotek Lestari, 2026)
The study was conducted with the aim of analyzing the suitability of land for shallot (Allium cepa L.) cultivation in Lampoko Village, Barebbo District, Bone Regency. The study was conducted from April to July 2025, using a combination of field surveys and laboratory tests. The approach used to evaluate land suitability was the matching method based on FAO standards. The results showed that soil in Lampoko Village generally had a pH ranging from 5.96 to 6.17 (slightly acidic to neutral), low total Nitrogen (0.15%-0,17%), and low available Phosphate (10.51-11,61 ppm). However, the soil has the advantage of high Cation Exchange Capacity (CEC) and Potassium availability that varies from very low to moderate. The evaluation results show that the actual land suitability class is S3n (Marginally Suitable) with the main limiting factor being nutrient availability (especially Phosphate. Through improvement efforts such as balanced N, P, and K fertilization and the addition of orgonic matter, the suitability class can be upgraded to Potential S2n (Moderately Suitable). This study concluded that Lampoko Village has the potential for shallot development, provided that location-specific nutrient management is applied to overcome phosphorus deficiency.